Canon law a comparative study with Anglo-American legal theory - Coughlin, John J., 1954- (New York ; Oxford : Oxford University Press, 2011)
'Canon Law' explores the canon law of the Roman Catholic Church from a comparative perspective. The introduction to the book presents historical examples of antinomian and legalistic approaches to canon law.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Canon law; Common law; Catholics -- Legal status, laws, etc. -- United States